The Global Economic Crisis and its Effects in Romania - Alexandru Trifu (Journal of Social and Development Sciences, 2012)
The crises represent malfunctions that may occur within every domain of the human activity. That is why the causes, their way of emergence and their consequences are studied. The crisis is analyzed by economists considering specific criteria, these offering it the characteristics of a phenomenon with poisonously consequences for the affected organizations, institutions and social groups: inflation, unemployment, stagnation, recession etc. The evolution of the financial crisis will lead economies into a deflationary spiral in the next year or even a longer lasting, as deficit reduction efforts will take large, and probably we shall assist an output of some euro area of weaker states. World economies are hit by this crisis to various extents, depending on the vulnerabilities of each and their exposure to toxic assets. The response to the crisis is contingent upon the fundamental principles we believe in, the available resources, the institutions and the instruments we can make use of. In Romania, the response to the adverse effects of the crisis cannot be similar to that made by some European countries or the U.S. There are several differences between the Romanian economy and these economies, which do not allow copying the package of measures developed there.